Paciente de sexo masculino de 59 años de edad presenta diabetes mellitus tipo ii descompensada e inadecuados hábitos alimenticios. - Díaz Tapia, Wendy Paola (2020)
This case study presents a 59-year-old male patient with uncontrolled Type 2 Diabetes and inadequate eating habits. Type 2 diabetes is a chronic disorder that affects the way in which the body metabolizes sugar (glucose), an important source of fuel for the body. With type 2 diabetes, the body resists the effects of insulin (hormone that allow cells of the body to take in glucose), or it does not produce enough insulin to maintain normal glucose levels. Nutritional therapy is a fundamental element in the treatment of type 2 diabetes mellitus, both for the prevention of its development and to avoid the complications that it entails. It is difficult to fulfill a nutritional plan because of the lifestyle changes that it implies. In any case, the social and cultural dietary patterns of each population must be taken to achieve good adherence. In addition to have a good glycemic control, dietary measures must be aimed to control the different cardiovascular risk factors such as hypertension (hypertension), dyslipidemia and obesity, trying to achieve a decrease in diabetes complications in the long term. The objective of this clinical case is to assess the nutritional status of the patient and prescribe a nutritional diet adapted to thee need of the patient, taking into account the universal general principles applied in Nutrition and Dietetics. In addition, the respective nutritional counseling is provided and the conclusion determine the nutritional status of the patient, evidencing the comprehensive nutritional diagnosis with the following indicators: Anthropometric, biochemical, clinical / physical and dietary evaluation, meal plan according to the nutritional needs of the patient with an example menu, and recommendations